Emerging Infections of CNS: Avian Influenza A Virus, Rift Valley Fever Virus and Human Parechovirus - Wiley, Clayton A. (Brain Pathol, 2015)
History is replete with emergent pandemic infections that have decimated the human population. Given the shear mass of humans that now crowd the earth, there is every reason to suspect history will repeat itself. We describe three RNA viruses that have recently emerged in the human population to mediate severe neurological disease. These new diseases are results of new mutations in the infectious agents or new exposure pathways to the agents or both. To appreciate their pathogenesis, we summarize the essential virology and immune response to each agent. Infection is described in the context of known host defenses. Once the viruses evade immune defenses and enter central nervous system (CNS) cells, they rapidly co‐opt host RNA processing to a cataclysmic extent. It is not clear why the brain is particularly susceptible to RNA viruses; but perhaps because of its tremendous dependence on RNA processing for physiological functioning, classical mechanisms of host defense (eg, interferon disruption of viral replication) are diminished or not available. Effectiveness of immunity, immunization and pharmacological therapies is reviewed to contextualize the scope of the public health challenge. Unfortunately, vaccines that confer protection from systemic disease do not necessarily confer protection for the brain after exposure through unconventional routes.